Code-Mixing: A Strategic Communication Practice Found in Cinta Laura’s Podcast - I Komang Sulatra; Desak Putu Eka Pratiwi (Universitas Islam Negeri Palopo, 2026)
This study examines the phenomenon of code-mixing in contemporary digital discourse, specifically focusing on narrative podcasts. The study mainly aims to find out type of code mixing and analyzing the function of code-mixing in podcast. Using a descriptive qualitative approach, the study analyzes an episode of the iWil Network podcast featuring Cinta Laura Kiehl, a prominent bilingual figure in Indonesia. The data were collected through observation method by applying several techniques, such as; making verbatim transcription, taking notes and categorizing the data of code-mixing according to Hoffman (1991) typology of intra-lexical mixing, intra-sentential mixing, and code-mixing involving a change of pronunciation. Audience Design Theory by Bell (1984) was applied to explore the functions of code-switching. The findings reveal a total of 124 instances of code-mixing, dominated by intra-Sentential mixing (21%) and followed by intra-lexical mixing (79 %). Meanwhile code-mixing involving a change of pronunciation did not occur in Cinta’s Utterances, since she is very fluent in English, therefore there was no pronunciation interference. These results indicate that code-mixing serves as a functional communication strategy to enrich Indonesian conversation through lexical borrowing and discourse tags while maintaining interactional fluency. The findings show that code-switching is used strategically to emphasize important information, express identity and solidarity, clarify meaning, and index modernity and expertise